Lanthanide and Heavy Metal Free Long White Persistent Luminescence from Ti Doped Li–Hackmanite: A Versatile, Low‐Cost Material. (17th March 2017) - Norrbo, Isabella; Carvalho, José M.; Laukkanen, Pekka; Mäkelä, Jaakko; Mamedov, Fikret; Peurla, Markus; Helminen, Hanna; Pihlasalo, Sari; Härmä, Harri; Sinkkonen, Jari; Lastusaari, Mika
Abstract : Persistent luminescence (PeL) materials are used in everyday glow‐in‐the‐dark applications and they show high potential for, e.g., medical imaging, night‐vision surveillance, and enhancement of solar cells. However, the best performing materials contain rare earths and/or other heavy metal and expensive elements such as Ga and Ge, increasing the production costs. Here, (Li, Na)8 Al6 Si6 O24 (Cl, S)2 :Ti, a heavy‐metal‐ and rare‐earth‐free low‐cost material is presented. It can give white PeL that stays 7 h above the 0.3 mcd m −2 limit and is observable for more than 100 h with a spectrometer. This is a record‐long duration for white PeL and visible PeL without rare earths. The material has great potential to be applied in white light emitting devices (LEDs) combined with self‐sustained night vision using only a single phosphor. The material also exhibits PeL in aqueous suspensions and is capable of showing easily detectable photoluminescence even in nanomolar concentrations, indicating potential for use as a diagnostic marker. Because it is excitable with sunlight, this material is expected to additionally be well‐suited for outdoor applications. Abstract : Lanthanide and heavy‐metal‐free material with long white persistent luminescence is developed from synthetic hackmanite. The material is suited for use as a single phosphor in lighting combined with emergency signage, and the material shows high potential for replacing lanthanide‐based label technologies. Because it is excitable with sunlight, the hackmanite material is excellent for new luminescence point‐of‐care detection technologies.